Cystic Artery Pseudoaneurysm with Concurrent Cholecystoduodenal Fistula—Endovascular Management and Review of Literature - Patidar, Yashwant; Chandel, Karamvir; Chatterjee, Navojit; Tripathy, Tara Prasad; Kumar, Senthil (Journal of Clinical Interventional Radiology ISVIR, 2022)
A rare complication of acute cholecystitis is a pseudoaneurysm of the cystic artery. We discuss a case of a 65-year-old man with synchronous cholecystoenteric fistula and cystic artery pseudoaneurysm managed by selective angioembolization of the cystic artery, followed by interval cholecystectomy.
Keywords: cystic artery pseudoaneurysm; angioembolization; n-BCA glue